Testing the Various Pathways Linking Forest Cover to Dietary Diversity in Tropical Landscapes - Baudron, Frédéric; Tomscha, Stephanie A.; Powell, Bronwen; Groot, Jeroen C. J.; Gergel, Sarah E.; Sunderland, Terry (Frontiers in Sustainable Food Systems, 2019)
A diverse diet is important to address micronutrient deficiencies and other forms of malnutrition, one of the greatest challenges of today’s food systems. In tropical countries, several studies have found a positive association between forest cover and dietary diversity, although the actual mechanisms of this has yet to be identified and quantified. Three complementary pathways may link forests to diets: a direct pathway (e.g., consumption of forest food), an income pathway (income from forest products used to purchase food from markets), and an agroecological pathway (forests and trees sustaining farm production). We used piece-wise structural equation modelling to test and quantify the relative contribution of these three pathways for households in seven tropical landscapes in Bangladesh, Burkina Faso, Cameroon, Ethiopia, Indonesia, Nicaragua and Zambia. We used survey data from 1,783 households and determined forest cover within a 2 km radius of each household. The quality of household diets was assessed through four indicators: household dietary diversity and consumption of fruits, vegetables and meat, based on a 24-hour recall. We found evidence of a direct pathway in four landscapes (Bangladesh, Cameroon, Ethiopia, and Zambia), an income pathway in none of the landscapes considered, and an agroecological pathway in three landscapes (Bangladesh, Ethiopia, and Indonesia). We also found evidence of improved crop and livestock production with greater forest cover in five landscapes (Bangladesh, Burkina Faso, Cameroon, Ethiopia, and Indonesia). Conversely, we found negative associations between forest cover and crop and livestock production in three landscapes (Cameroon, Indonesia, and Zambia). In addition, we found evidence of forest cover being negatively related to at least one indicator of diet quality in three landscapes (Indonesia, Nicaragua and Zambia), and to integration to the cash economy in three landscapes (Cameroon, Ethiopia, Nicaragua). This is one of the first studies to quantify the different mechanisms linking forest cover and diet. Our work illuminates the fact that these mechanisms can vary significantly from one site to another, calling for site-specific interventions. Our results also suggest the positive contributions of forests to rural livelihoods cannot be generalized and should not be idealized.